Values assessment for personnel selection: comparing job applicants to non-applicants - Anglim, Jeromy; Molloy, Karlyn; Dunlop, Patrick; Albrecht, Simon; Lievens, Filip; Marty, Andrew (2021)
Some scholars suggest that organizations could improve their hiring decisions by measuring the personal values of job applicants, arguing that values provide insights into applicants’ cultural fit, retention prospects, and performance outcomes. However, others have expressed concerns about response distortion and faking. The current study provides the first large-scale investigation of the effect of the job applicant context on the psychometric structure and scale means of a self-reported values measure. Participants comprised 7,884 job applicants (41% male; age M = 43.32, SD = 10.76) and a country-, age-, and gender-matched comparison sample of 1,806 non-applicants (41% male; age M = 44.72, SD = 10.97), along with a small repeated-measures, cross-context sample. Respondents completed the 57-item Portrait Values Questionnaire (PVQ) measuring Schwartz’ universal personal values. Compared to matched non-applicants, applicants reported valuing power and self-direction considerably less, and conformity and universalism considerably more. Applicants also reported valuing security, tradition, and benevolence more than non-applicants, and reported valuing stimulation, hedonism, and achievement less than non-applicants. Despite applicants appearing to embellish the degree to which their values aligned with being responsible and considerate workers, invariance testing suggested that the underlying structure of values assessment is largely preserved in job applicant contexts.